RANCANG BANGUN DIPLEKSER UNTUK PEMANCAR TELEVISI ULTRA HIGH FREQUENCY (UHF) - Trie Handayani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2009)
The development of television technology in Indonesia has growth rapidly. This fast growth is marked by the presence of 10 private television stations. Establishing a television station requires a lot of expense especially to build transmitter and tower antenna. This paper presents a research to design and built the diplexer system for merging two transmitter signals transmitted by an antenna transmitter. This design is conducted by using two copper pipes with diameter 3.2 cm and 1.4 cm. The use of different sizes of diameter is intended to obtain impedance characteristic (ZO) equal to 50 Ω. The copper pipe is designed to form a system diplexer with open and close end of transmission. There are two mixing frequency tested, those are 620 MHz ( at terminal A) and 600 MHz (at terminal B). The result shows that terminal A acts as a band pass filter for frequency around 620 MHz and a filter stop band for frequency around 600 MHz . Terminal B acts as a band pass filter for frequency around 600 MHz and as a stop band for frequency around 620 MHz. Based on the results obtained,  this diplexer can be applied to merge two television transmitters with carrier frequency of 600 MHZ and 620 MHz within a single antenna.